Correction to: Dahl-Popolizio, S., Carpenter, H., Coronado, M., Popolizio, N. J., & Swanson, C. (2020). Telehealth for the provision of occupational therapy: Reflections on experiences during the COVID-19 pandemic - Ellen R. Cohn (International Journal of Telerehabilitation)
Correction to: Dahl-Popolizio, S., Carpenter, H., Coronado, M., Popolizio, N. J., & Swanson, C. (2020). Telehealth for the provision of occupational therapy: Reflections on experiences during the COVID-19 pandemic. International Journal of Telerehabilitation, 12(2), 77–92. https://doi.org/10.5195/ijt.2020.6328